Interpersonal Communication in the workplace in the perspective of People with Disability co-workers - Nogueira, Marta (2022)
This study aimed to analyze how Interpersonal Communication (IC) is processed in an organization that works with People with Disability (PwD) from the point of view of co-workers. A total of 314 PwD co-workers, employees of Auchan Portugal Group, participated in this study. The quantitative methodology was used, with recourse to a semi-structured questionnaire. Data analysis was carried out through descriptive and inferential statistics, using SPSS-24.0 (Statistical Package for the Social Sciences) software. The results showed that of all the items in the IC dimension, those that presented a higher degree of agreement were: "In general there is good communication with the PwD" and "The PwD has contact/interaction with the different workers/departments". Those with a lower level of agreement were: "PwD usually have problems in relating to colleagues" and "PwD may adopt inadequate behavior and attitudes in organizations". From the correlation analysis, a statistically significant correlation was verified between the academic qualifications of the PwD's colleagues and the item "The PwD is more communicative than the others". From the analysis of the differences according to professional position, statistically significant differences were found between the groups "Supervisor/Responsible" and "Worker" in three items of the IC. This study aims to contribute to a greater knowledge about the reality of PwD experienced in the workplace and to the increase of good practices by organizations.